Matched or nonmatched interventions based on the transtheoretical model to promote physical activity. A meta-analysis of randomized controlled trials - Ahmed Jerôme Romain; Catherine Bortolon; Mathieu Gourlan; Marion Carayol; Emmanuelle Decker; Olivier Lareyre; Grégory Ninot; Julie Boiché; Paquito Bernard (Elsevier, 2018)
Purpose: The aim of this study was to examine whether the efficacy of transtheoretical model (TTM)-based interventions on physical activity (PA) varied according to the following criteria: (1) interventions targeted the actual stages of change (SOCs) or did not; (2) participants were selected according to their SOC or were not; and (3) its theoretical constructs (decisional balance, temptation, self-efficacy, processes of change). Methods: Thirty-three randomized controlled trials assessing TTM-based interventions promoting PA in adults were systematically identified. Results: The between-group heterogeneity statistic (Qb) did not reveal any differential efficacy either in interventions targeting the actual SOC compared with those that did not (Qb = 1.48, p = 0.22) or in interventions selecting participants according to their SOC compared with those that did not (Qb = 0.01, p = 0.91). TTM-based interventions enhanced PA behavior whether they targeted the actual SOC (Cohen's d = 0.36; 95% confidence interval (CI): 0.22-0.49) or not (d = 0.23; 95%CI: 0.09-0.38) and whether they selected their participants according to their SOC (d = 0.33; 95%CI: 0.13-0.53) or not (d = 0.32; 95%CI: 0.19-0.44). The moderators of the efficacy of TTM-based interventions were the number of theoretical constructs used to tailor the intervention (Qb = 8.82, p = 0.003), the use of self-efficacy (Qb = 6.09, p = 0.01), and the processes of change (Qb = 3.51, p = 0.06). Conclusion: TTM-based interventions significantly improved PA behavior, and their efficacy was not moderated by SOC but by the TTM theoretical constructs.